Infestation levels of Anastrepha fraterculus, Ceratitis capitata and Drosophila suzukii in different fruit species in the department of Concordia, Entre Ríos - Viana, Valeria Angelica; Liendo, María Clara; Segura, Diego Fernando; Telayna, Jose Carlos; Bouvet, Juan Pedro (FAO-IAEA, 2024)
Póster